CHARACTERISTICS OF PURSEâCOWPEA COMPOSITE FLOUR BISCUITS ON DIFFERENT TYPES OF PACKAGING DURING STORAGE - Tri Rahayuningsih, Endang Retno Wedowati, Diana Puspitasari, Fungki Sri Rejeki & (Proceeding of International Congress, 2014)
Purse (Xanthosoma sagitifolium) is one type of tubers that have the potential for an alternative as a foodsource. Innovation for product needs to be done to exploit the potential of the purse. One form of theproducts that can be an alternative is purse biscuit. It is expected that purse biscuit will have a higher economicvalue. To improve nutrition in highâcarbohydrate purse then added cowpea flour to increase theprotein content in biscuits. Based on this background, this study aims to determine the character of thepurseâcowpea composite flour biscuits, as well as knowing the shelf lifeâs biscuits in various types of packagingmaterials. Results showed treatmentâselected purseâcowpea composite flour in the composition 50%purse flour and 50% cowpea flour. While the flour formula to made biscuit products are selected on compositeflour of 60% purseâcowpea flour and 40% wheat flour. While thatâs flour formula have characteristics,namely: 2,790% Moisture content, 1,627% ash content, 50,080% carbohydrate content, 6,580% proteincontent, fat content 35,113%, and 210,030% raise power. Based various types of packaging(polypropilene plastic, polyethilene plastic, and aluminum foil) during productâs storage, the selectedtreatment results obtained using the storage of aluminum foil with a total expected value 7,06 with assessmentcriteria are moisture content, ash content, carbohydrate content, protein content, fat content, andTPC.Keywords: purse, cowpea, biscuits, composite flour